2020
DOI: 10.3389/fphys.2020.00148
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV as a Muscle Myokine

Abstract: Dipeptidyl peptidase IV (DPP-IV) is a unique serine protease that exists in a membrane bound state and in a soluble state in most tissues in the body. DPP-IV has multiple targets including cytokines, neuropeptides, and incretin hormones, and plays an important role in health and disease. Recent work suggests that skeletal muscle releases DPP-IV as a myokine and participates in control of muscle blood flow. However, few of the functions of DPP-IV as a myokine have been investigated to date and there is a poor u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In recent years, research has shown that skeletal muscles release DDP-4 as a myokine and could regulate muscular blood flow. 136 DPP-4 inhibitors inhibited loss of muscle mass in older patients with type 2 diabetes. 137 Furthermore, compared with SU drugs, DPP-4 inhibitors inhibited the progression of loss of muscle mass and sarcopenia.…”
Section: Incretin Modulatorsmentioning
confidence: 98%
“…In recent years, research has shown that skeletal muscles release DDP-4 as a myokine and could regulate muscular blood flow. 136 DPP-4 inhibitors inhibited loss of muscle mass in older patients with type 2 diabetes. 137 Furthermore, compared with SU drugs, DPP-4 inhibitors inhibited the progression of loss of muscle mass and sarcopenia.…”
Section: Incretin Modulatorsmentioning
confidence: 98%
“…In addition to what we have summarized above, with the development of biotechnology, more and more myokines have been discovered, such as Apelin ( 116 ), Chitinase-3-like protein ( 117 ), Follistatin-like 1 ( 118 ), Dipeptidyl Peptidase IV ( 119 ), MG53 ( 120 ) and METRNL ( 121 ), which they also play a key role in maintaining the human homeostasis of the body. Further studies are needed to determine whether they are related to DN and, if so, how Table 1 .…”
Section: Myokines and Dnmentioning
confidence: 99%
“…Skeletal muscles (SM) comprise the largest organ in the body, and thus, process the largest amounts of administered drugs [ 62 ]. Furthermore, muscle has recently been reported to release DPP-4 [ 63 ]. SM cell cultures were observed to release DPP-4 during differentiation [ 64 ], and DPP-4 activity in the bathing medium from intact SM was found to be enhanced by whey protein in situ [ 65 ].…”
Section: Dpp-4 Inhibition and Skeletal Muscle Functionmentioning
confidence: 99%